Teaching children science : hands-on nature study in North America, 1890-1930 - Kohlstedt, Sally Gregory, 1943- (University of Chicago Press, 2010)
The definitive history of nature study, this book emphasizes the scientific, pedagogical, and social incentives that encouraged primarily women teachers to explore nature in and beyond their classrooms in North America from 1890 to 1930.